Fibrinolytic Protease Production: Impact of Initial pH and Temperature in Solid-State Fermentation by Rhizopus microsporus var. oligosporus FNCC 6010 - Rebhika Lusiana; Achmad Toto Poernomo; Achmad Syahrani (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Fibrinolytic enzyme is one of the cardiovascular disease therapies. Rhizopus microsporus var. oligosporus is microorganism that has been evaluated to produce fibrinolytic protease by fermentation. This study conducted fermentation of helianthi annui semen (sunflower seed) by Rhizopus microsporus var. oligosporus to produce fibrinolytic enzyme. Objective: This study aims to determine the effect of Initial pH and incubation temperature and its optimization in the production of fibrinolytic protease by Rhizopus microsporus var. oligosporus FNCC 6010 in solid-state fermentation on helianthi annui semen (sunflower seed) substrate.  Optimum condition was determined by maximum protease and fibrinolytic activity. Method: A crude enzyme of protease fibrinolytic was obtained from the supernatant extract of fermented sunflower seed. Protease activity was measured by the skimmed milk agar (SMA) plate method, and fibrinolytic activity was determined by the fibrin agar plate method. Result: It was found that the starting pH affects both the proteolytic and fibrinolytic activity of enzymes that are produced in fermentation. The starting pH of 5.0 showed higher fibrinolytic and proteolytic activity values compared to the starting pH of 7.0. The incubation temperature 33±1 °C had the higher activity compared to 28±1 °C or 37±1 °C. Conclusion: Initial pH and incubation temperature affect the proteolytic and fibrinolytic activity of crude enzyme extracted from fermented sunflower seed by Rhizopus microsporus var. oligosporus. The optimum condition for producing fibrinolytic protease in the state fermentation method was an initial pH of 5.0 and an incubation temperature of 33±1°C.